2018
DOI: 10.1155/2018/5101656
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hypoglycaemic and Antiobesity Effects of Senna italica Leaf Acetone Extract

Abstract: Background Type II diabetes is on the rise while obesity is one of the strongest risk factors of type II diabetes. The search for a drug for type II that can equally mitigate obesity related complication is desired. Methods The acetone leaf extract of Senna italica was evaluated for its cytotoxic, antiglycation, and lipolytic effect, glucose uptake, and GLUT4 translocation and expression using published methods, while that for adipogenesis and protein expression levels of obesity related adipokines was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…We were able to identify two extracts (4404 and 4407) prepared from Bellis perennis (common daisy) as potent compound mixtures capable of inducing GLUT4 translocation. Concentrations of only 250–500 µg/L, which are 100–1000 times lower than the one reported for various others, mainly ethanolic/methanolic, plant extracts [ 42 , 43 , 44 , 45 , 46 ], resulted in a significant increase of GLUT4 molecules in the plasma membrane. Additionally, the homemade ethanolic Bellis perennis extract prepared from raw material collected from the local area proved to be even more potent in inducing GLUT4 translocation.…”
Section: Discussionmentioning
confidence: 56%
“…We were able to identify two extracts (4404 and 4407) prepared from Bellis perennis (common daisy) as potent compound mixtures capable of inducing GLUT4 translocation. Concentrations of only 250–500 µg/L, which are 100–1000 times lower than the one reported for various others, mainly ethanolic/methanolic, plant extracts [ 42 , 43 , 44 , 45 , 46 ], resulted in a significant increase of GLUT4 molecules in the plasma membrane. Additionally, the homemade ethanolic Bellis perennis extract prepared from raw material collected from the local area proved to be even more potent in inducing GLUT4 translocation.…”
Section: Discussionmentioning
confidence: 56%
“…It is mostly intracellular in the unstimulated state but is acutely redistributed to the PM in response to insulin, contraction, and other stimuli [ 9 ]. The amount of glucose uptake is determined by the number of GLUT4 molecules on the muscle cell membranes [ 36 , 45 ]. Relevant studies reported that GLUT4 translocation and fusion with PM were the main rate-limiting steps for glucose disposal [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thilagam et al discovered that the ethanolic leaf extract of Senna surattensis inhibited the carbohydrate digestive enzymes and increased the peripheral glucose uptake in the isolated rat hemidiaphragm model [ 34 ]. Malematja et al showed that Senna italica leaf acetone extract promoted glucose uptake and anti-obesity through the PI3K-dependent pathway [ 36 ]. However, only a few studies have assessed the possible hypoglycemic properties and hypoglycemic mechanisms of Folium Sennae (FSE).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the antidiabetic activity of Senna plants due to the content of phenols and flavonoids [14]. The antidiabetic effects have as mechanisms the decrease of the expression levels of different adipokines and the reduction of glucose absorption [15].…”
Section: Introductionmentioning
confidence: 99%